Modulation of Mammary Gland Development and Milk Production by Growth Hormone Expression in GH Transgenic Goats - Bao, Zekun (Front Physiol, 2016)
Mammary gland development during puberty and reconstruction during pregnancy and lactation is under the control of circulating endocrine hormones, such as growth hormone, which are released from the pituitary. In this study, we explored the influence of overexpression of growth hormone in the mammary gland on breast development and milk production in goats. Using transcriptome sequencing, we found that the number of highly expressed genes was greater in GH transgenic goats than non-transgenic goats. Furthermore, KEGG pathway analysis showed that the majority of the genes belonged to the MAPK signaling pathway and the ECM-receptor interaction pathway. The expression of genes related to breast development was further confirmed using qRT-PCR. Interestingly, both milk production and milk quality were increased. The results of these experiments imply that overexpression of growth hormone in the breast may stimulate breast development and enhances milk production by modulating alveolar cell proliferation or branching through the MAPK signaling pathway.